Neighborhood community and quality of life - O'Brien, David J.; McClendon, McKee J.; Ahmed, Ansar (Routledge, 2017)
This article was published in the Journal of the Community Development Society [© 1989 Routledge ] and the definite version is available at : http://dx.doi.org/10.1080/15575338909489983 The Journal's website is at: http://www.tandfonline.com/doi/abs/10.1080/15575338909489983